The Role of Brand Image, Price and Trust on Purchase Intention Herbal Medicine - Lalu Supardin; Heru Noor Rokhmawati; Heru Kuncorowati (SMARTINDO, 2023)
Purpose – This study aims to examine the role of brand image, price and trust on purchase intention Herbal Medicine in Special Region of Yogyakarta. The respondents in this study were consumers at Special Region of Yogyakarta. Design/methodology/approach – This study uses a quantitative approach. The number of respondents in this study were 100 respondents. Sampling is done by purposive sampling technique. This study uses multiple linear regression with SPSS as analytical tool. Originality – This research will be able to complete the gap regarding the consumption of herbal supplements both during the pandemic Covid-19 after the post-Covid 19 recovery period. Findings and Discussion – Based on the results of data testing conducted, it shows that: (1) Brand image has a significant effect on purchase intention Herbal Medicine in Special Region of Yogyakarta. (2) Price has a significant effect on purchase intention Herbal Medicine in Special Region of Yogyakarta. (3) Trust has a significant effect on purchase intention Herbal Medicine in Special Region of Yogyakarta. (4) Brand image, price and trust simultaneously significant effect on purchase intention Herbal Medicine in Special Region of Yogyakarta.